Aemilia Lanyer and Shakespeare's Helena - Yasmin Arshad (Opticon1826, 2010)
Not much is known about the middle class womenfrom the Elizabethan and Jacobean era who served the aristocracy and lived on its edge. Aemilia Lanyer and Shakespeare’s Helena, a real woman and a dramatic character, are two such women. By considering one of Shakespeare’s female characters alongside a real woman from the period who shared a similar social predicament, much may be learnt about the cultural position of women at the time, the limits upon women’s agency, and the efforts by some women to pursue their aspirations and desires within these limits. By taking this New Historicist approach we may also learn something about Shakespeare in the context of his time. This article will look at Lanyer, who served as a companion to the Countess of Cumberland, and Helena from All’s Well That Ends Well, who was a companion to the Countess Rossillion. It will examine their lives and choices and compare their situation with the aristocratic women they served. The article will look for parallels in the circumstances of all these women.
Keywords: feminism; patriarchy; shakespeare